2002
DOI: 10.1021/es010226h
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and Transport of Heavy Metals and Macroelements during Electroremediation

Abstract: Electroremediation makes treatment of contaminated clay soils possible. The external electrical field causes several transport processes and changes in soil chemistry. This study concerns the leachability and transport of calcium, magnesium, copper, zinc, lead, nickel manganese, chromium, and iron during treatment with an electric field of soil from a chlor-alkali factory. As expected, most elements were removed from the acidic part of the soil and accumulated in the zone where pH changed from acidic to alkali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 15 publications
4
18
1
2
Order By: Relevance
“…This increase in organic matter content when CA was used to treat sludge can be attributed to a change in the structure of the sludge (Jakobsen et al, 2004;Hahladakis et al, 2014;Suèr et al, 2003;Wang et al, 2015). In previous studies, Wang et al (2015) also observed increases after CA extraction; specifically, the organic matter content in the sludge from that study increased from 256.2 to 376.7 g/kg because of the residual citric acid, which may act as a nutrient source for fertilizers.…”
Section: Organic Mattermentioning
confidence: 52%
“…This increase in organic matter content when CA was used to treat sludge can be attributed to a change in the structure of the sludge (Jakobsen et al, 2004;Hahladakis et al, 2014;Suèr et al, 2003;Wang et al, 2015). In previous studies, Wang et al (2015) also observed increases after CA extraction; specifically, the organic matter content in the sludge from that study increased from 256.2 to 376.7 g/kg because of the residual citric acid, which may act as a nutrient source for fertilizers.…”
Section: Organic Mattermentioning
confidence: 52%
“…Although laboratory bench tests have demonstrated that ER has the potential to be effective for a variety of soil matrices, including clay, sand, and silt (Clifford et al, 1993;Hamed et al, 1991;Reed et al, 1996;Suèr et al, 2003;Wong et al, 1997), ER is most applicable to saturated soils with low groundwater flow rates and moderate to low permeability (Evanko & Dzombak, 1997).The use of ER is limited in highly conductive soil matrices (FRTR, 2001), because these matrices will require higher energy inputs to effect remediation. Features common to contaminated soil systems, such as the presence of iron oxide-rich zones or lenses of alkaline mineral, can limit the effectiveness of ER in field-scale applications and lead to incomplete treatment (Marceau & Broquet, 1999;Reddy & Chinthamreddy, 1999;Reddy & Parupudi, 1997;Yeung et al, 1996).…”
Section: Electrokinetic Remediationmentioning
confidence: 99%
“…Se ha demostrado su capacidad para remover algunos contaminantes orgánicos como tricloroetileno e hidrocarburos en estudios de laboratorio. La aplicación que se ha comunicado con más frecuencia es la de recuperación de suelos contaminados con metales pesados como Cr, Cd, Hg, Pb, Mn, Zn y As [10,11,12,13,14]. La EBR combina la aplicación de corriente eléctrica directa con técnicas de biorremediación asistida con nutrientes, aireación y agua.…”
Section: Introductionunclassified